Experimental study on the use of polyoxymethylene plastic waste as a granular column to improve the strength of soft clay soil - Muhammad Syamsul Imran, Zaini; Muzamir, Hasan; Sultan, Almuaythir (Nature Publishing Group, 2024)
The surging demand for sustainable and efficacious approaches of enhancing the ground has resulted in the investigation of novel waste materials. This study investigates the utilization of Polyoxymethylene (POM) as a granular column to ameliorate the ability of soft clay soil to resist horizontal loads. The study introduces a new implementation of polyoxymethylene columns as ground improvement approach to tackle the complexities related to soft clay soils. The capability of polyoxymethylene columns was analyzed through a sequence of laboratory experiments, containing engineering characteristic tests, unconfined compressive strength (UCS) tests, and consolidated isotropic undrained (CIU) triaxial tests. The effects of the number of columns, column diameter, column depth, substitute area ratio, depth penetration ratio, column aspect ratio, volume infusion ratio, and confining pressures, were evaluated to analyze the behavior of individual and clustered encapsulated polyoxymethylene columns. The findings verified a notable development in the ability of soft clay soil, when strengthened with polyoxymethylene columns, to oppose the lateral loads and maintain overall stability. Additionally, a regression analysis was implemented to establish a prediction model that estimates the increase in shear strength of POM columns based on different column dimensions. This model is a practical tool for evaluating the performance of reinforced soft clay soils in large-scale projects. This study not only accentuates the mechanical benefits of polyoxymethylene but also accentuates its environmental benefits, prescribing for the implementation of recyclable materials in ground renovation.